Dynamic changes in human THP-1-derived M1-to-M2 macrophage polarization during Thelazia callipaeda MIF induction - Yin, Changzhu; Cai, Juan; Gou, Yanting; Li, Di; Tang, Hongri; Wang, Lingjun; Liu, Hui; Luo, Bo (Frontiers in Immunology, 2023)
Macrophages are innate immune cells with essential roles in the immune response during helminth infection. Particularly, the direction of macrophage polarization could contribute to pathogen trapping and killing as well as tissue repair and the resolution of type 2 inflammation. This study establishes that the recombinant protein of Thelazia callipaeda macrophage migration inhibitory factor (T.cp-MIF) induces THP-1-derived macrophages to undergo M1 to M2 type dynamic polarization, using the methods of flow cytometry, real-time quantitative PCR, differential transcriptomic analysis and western blot. Interestingly, there was an increase in protein and mRNA expression of M1-type proteins and cytokines after the use of PI3K inhibitors, suggesting that the polarization state tends to favor the M1 type after M2 type inhibition. In conclusion, the dynamic polarization mechanism of T.cp-MIF-induced human THP-1-derived macrophages from M1 to M2 type is related to the binding of TLR4. It can first affect the M1 type polarization of macrophages by activating its downstream NF-κB pathway. Activation of the PI3K/Akt pathway and inhibition of NF-κB phosphorylation affects the M2 type polarization of macrophages.